Exploring the influence of cultural participation on the subjective well-being of victims in Mexico - Reyes-Martínez, Javier; Martínez-Martínez, Oscar A.; Lombe, Margaret; Piñeros-Leaño, María (Frontiers in Psychology, 2023)
Considering the increasing incidence of crime in Mexico, it is necessary to understand the strategies that individuals utilize in response to victimization and the effects of this on their subjective well-being. With data from the 2012 Self-reported Well-Being Survey (BIARE, n=10,654) and through a generalized structural equation modeling analysis, the main purpose of this manuscript is to understand whether cultural participation can moderate or mediate the effects of victimization on individuals’ subjective well-being. Results from the study show an overall positive influence of the cultural participation activities on the subjective well-being of victims of community and structural violence. This has implications for scholars, policymakers, and practitioners in the improvement of the general quality of life of victims